Information systems for regional labour market monitoring. State of the art and perspectives. - (:unkn) unknown (Hampp, 2009)
Ein auf web-basierten Arbeitsmarktinformationssystemen beruhendes Monitoring regionaler Arbeitsmärkte findet zunehmende Verbreitung. Der Sammelband zeigt die große Bandbreite derartiger Arbeitsmarktmonitore einzelner europäischer Länder. Dabei können generell zwei Systeme unterschieden werden. Das erste basiert auf regionalen Quellen, das zweite auf einem zentralen System mit regionalen Unterabteilungen. Darüber hinaus zeigen die Beiträge die Möglichkeiten der angewandten Informations- und Kommunikationstechnologie, weisen aber auch auf die Grenzen dieser Systeme hin.

Regional labour market monitoring based on web-based labour market information systems is becoming increasingly more common. This anthology shows the variety of such systems as implemented in various European countries. Two general types can be distinguished. The first are regionally-based information tools and secondly, national systems with regional sub-divisions. In addition, these show what information and communication technologies make possible, but they also give the first indications of where these technologies have their limits. This volume should trigger a wider discussion in this field. This book was developed by several members of the European Network of Regional Labour Market Monitoring.
Keywords: Arbeitsmarkt; Arbeitsmarktstatistik; Region; Regionalisierung; Informationssystem; Vergleich; Monitoring; Arbeitsmarktentwicklung; Arbeitsmarktbeobachtung; Netzwerk